About One Memorable Date in the History of Spain - G. I. Volkova (Vestnik MGIMO-Universiteta)
In 1714 the Catalans, being in the camp of the losers in the War of the Spanish Succession, finally lost any hope to gain independence. 300 years later, nationalists, who are in power now in Catalonia, want to take advantage of that memorable date by organizing a regional referendum in order to choose their own path of development. In the aggravating conflict of interests between Madrid and Barcelona both parties use not only political and propaganda measures, but also financial leverages of influence. The ethnonational issue in the multiethnic Spain is far from being solved, because for centuries the process of forming a unified Spanish state was characterized by political union of several genetically related (except Basque) ethnic communities, although with significant socio-cultural and linguistic differences among them. It is not coincidental that regional identity in Spain is still extremely strong, while the interethnic consolidation of the Spanish nation can be characterized as incomplete, which can be seen, particularly, in the intensification in recent decades of radical nationalist and separatist sentiments in Catalonia, the Basque Country and some other autonomies. Among reasons which escalated confrontation between supporters and opponents of Catalonian independence, we should mention the global financial crisis that hit the regions of Spain as well as the overall national economy. The separatists have many barriers on their way, starting from the constitutional provisions proclaiming Spain a united and indivisible state which impede to carry out regional plebiscites, and ending by an ambiguous attitude towards the hypothetical independence of Catalonia by both the residents of the region and in other parts of the country. It is important to keep in mind that in today's world the possibility of breaking large multiethnic state into ethnically constituting elements is more possible than 40-50 years ago. Disintegration of Yugoslavia and the Soviet Union and the emergence on the world political map of Abkhazia, South Ossetia, and most recently of the Republic of Crimea - confirm this. The Catalonian nationalists in their arguments in favor of the sovereignty of Catalonia refer to the arbitrariness of the borders formed in the past between separate European countries and the regions. Modern state boundaries indeed are not the result of rational planning, democratic arrangements or consideration of the local population's opinion. In many ways, the current borders are the result of historical processes, often - of bloody wars and territorial annexations. In other words, they are the result of actions which are contrary to current international law and moral norms of behavior. Independent Catalonia is still a hypothesis, but under certain conditions and, more importantly, as a result of concerted efforts of regional nationalists it could become a reality.